PREVALENCE OF ALLERGIC REACTIONS AMONG MEDICAL UNIVERSITY STUDENTS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
Epidemiological studies over the past decades show that the prevalence of allergic diseases continues to increase, especially in developed countries. Diseases such as atopic dermatitis, allergic rhinitis, and bronchial asthma affect a huge number of people around the world. Factors leading to allergic reactions include hereditary predisposition, disorders of the nervous and endocrine systems, frequent infections, bad habits, and environmental pollution with various xenobiotics.